Aboriginal Peoples Survey, 2012 [Education and Employment Experiences Data] [Canada] [Excel] ... : APS 2012 ... - Social And Aboriginal Statistics Division. (Borealis, 2023)
Additional data tables that support the study, Analytical Paper: The Education and Employment Experiences of First Nations People Living Off Reserve, Inuit, and Métis: Selected Findings from the 2012 Aboriginal Peoples Survey [pdf] The 2012 Aboriginal Peoples Survey (APS) is a national survey of First Nations people living off reserve, Métis and Inuit aged six years and over. The 2012 APS represents the fourth cycle of the survey. It was designed to be thematic; questions emphasize education and employment, with a health supplement. It also collects information on language, income, housing and mobility.The APS complements other sources of information, including the Canadian Census of Population and the National Household Survey (NHS). Following the release of data from the 2006 APS, a content review was conducted to ensure the future relevance of existing APS questions to key stakeholders and to identify any potential data gaps. The review brought together expertise from a diverse group of researchers and ... : Version Date: 2013-11-25Version Text: Version 1 Notes: Contrary to 2001 and 2006, the 2012 target population no longer covers the Aboriginal ancestry-only population and no longer covers Indian reserves and First Nations communities in the territories. In the provinces, certain Indian reserves and settlements were covered in 2001 and most of them were covered in 1991. ...